Psychological and social problems and mechanisms of older person's care - djaballah, tayeb; Lamouri, nacira; Battaoui, bahia (Al-Jamie Journal In Psychological Studies and Educational Sciences, 2021)
Ageing is the Advanced or final stage of human life,with many changes often associated with debilitation and vulnerability. It has a direct impact on its life and thus suffers from several, particular, psychological and social problems. In view of the fact that, the category of older persons are considered to be the segments of society that need serious attention and special care for religions, humanitarian, social Ans ethical considerations. This category have been studied by scientistes and specialists to learn about their psychology, interests, needs and problems. As well as to identify cure or therapy, preventive methods and providing adequate care too. On this basis, awarness and need have emerged in many countries to take all necessary mesures to protect the elderly. In turn, since independance, Algeria has sought to care this category, and the ministry of National Solidarity, Family and Women’s Issues had been established. Its tasks includes caring for the elderly and ensuring that structure are established for them, to take care and provide comprehensive for them. In the part of this research paper, we will try to determine the importance of the topic, its objectives and its basic concepts, by highlighting the major problems experienced by older persons, particularly psycho-social ones. And then, we discussed theories that explain these problems afterwards. Then, we overviewing the main methods used and adopted by the Algerian State in caring this category. We take about the role of the family. As it considered as the first poster care for the elderly. Finally, we made recommendations and solutions to confront and overcome these problems.